Liver stiffness by magnetic resonance elastography is associated with increased risk of cardiovascular disease in patients with non‐alcoholic fatty liver disease. Issue 9 (25th March 2021) - Park, Jung Gil; Jung, Jinho; Verma, Kritin K.; Kang, Min Kyu; Madamba, Egbert; Lopez, Scarlett; Qas Yonan, Aed; Liu, Amy; Bettencourt, Ricki; Sirlin, Claude; Loomba, Rohit
Summary: Background: Magnetic resonance elastography (MRE) is a reliable non‐invasive alternative to liver biopsy for assessing liver fibrosis. There are limited data regarding an association between liver fibrosis by MRE and risk of cardiovascular disease (CVD). Aim: To investigate the association of high‐risk CVD phenotype determined by coronary artery calcification (CAC) with liver fibrosis by MRE in patients with non‐alcoholic fatty liver disease (NAFLD). Method: This was a cross‐sectional analysis of well‐characterised, prospective cohorts including 105 patients with NAFLD (MR imaging‐derived proton density fat fraction ≥ 5%) with contemporaneous cardiac computed tomography (CT) and MRE. Patients were assessed using MRE for liver stiffness, and cardiac CT for the presence of CAC (defined as coronary artery calcium score > 0). Odds of presence of CAC were analysed using logistic regression analysis. Results: The average age and body mass index were 54.9 years and 32.9 kg/m 2 respectively. In this cohort, 49.5% of patients had CAC and 35.2% had significant liver fibrosis (defined as MRE ≥2.97 kPa). Compared to patients without CAC, those with CAC were older (50.0 [39.0‐59.0] vs 63.0 [55.5‐67.5], P < 0.001) and had higher Framingham risk score (FRS, 1.0 [0.5‐3.5] vs 6.0 [2.0‐12.0], P < 0.001). In multivariable‐adjusted analysis, liver stiffness as a continuous trait on MRE was independently associated with the presence of CAC in a sex and age‐adjusted model (adjusted odd ratios [aOR] = 2.23, 95% confidence interval [CI] = 1.31‐4.34, P = 0.007) as well as in a FRS‐adjusted model (aOR = 2.16, 95% CI = 1.29‐4.09, P = 0.008). When analysed as a dichotomous trait, significant fibrosis (MRE‐stiffness ≥2.97 kPa) remained independently associated with the presence of CAC in both FRS‐adjusted model and sex and age‐adjusted model (aOR = 3.21‐3.53, P = 0.013‐0.017). In addition, CAC was more prevalent in patients with significant fibrosis than those without as determined by MRE (67.6% vs 39.7%, P = 0.012). Conclusion: Liver stiffness determined by MRE is an independent predictor for the presence of CAC in patients with NAFLD. Patients with NAFLD and significant fibrosis by MRE should be considered for further cardiovascular risk assessment, regardless of their FRS. Abstract : Liver stiffness determined by magnetic resonance elastography predicts prevalence of coronary artery calcification regardless of Framingham Risk Score.